Effect of Medicare Home Health Care Payment on Informal Care - Ezra Golberstein; David C. Grabowski; Kenneth M. Langa; Michael E. Chernew (SAGE Publishing, 2009)
This paper assesses the effect of payment caps for Medicare home health care on the use of informal care by older adults with functional limitations. We find that individuals exposed to more restrictive payment caps offset reductions in Medicare home health care with increased informal care, although we only observe this effect for lower-income individuals. This suggests that home care payment restrictions may have increased the caregiving burden on some low-income families, but that many higher-income families were able to either forgo the care or finance it privately. Home care payment policies should recognize these effects, balancing costs of the program with the desire to protect families from the burdens associated with providing informal home care.